Type I interferon receptor in peripheral blood mononuclear cells may predict response to intra-arterial 5-fluorouracil + interferon therapy for advanced hepatocellular carcinoma - Korenaga K (Dove Medical Press, 2011)
Yasuyuki Tomiyama1, Naoko Yoshioka1, Yoshiaki Yanai2,3, Tomoya Kawase1, Sohji Nishina1, Yuichi Hara1, Koji Yoshida1, Keiko Korenaga1, Masaaki Korenaga1, Keisuke Hino11Department of Hepatology and Pancreatology, Kawasaki Medical University, Kurashiki, Japan; 2Institute of Fujisaki, Hayashibara Biochemical Lab Inc, Okayama, Japan; 3Pharmaceutical Marketing Division, Otsuka Pharmaceutical Co Ltd, Tokyo, JapanBackground: Type 1 interferon alpha receptor 2 (IFNAR2) in the liver has been reported to be a predictive factor for the response to intra-arterial 5-fluorouracil (5-FU) + systemic interferon (IFN)-alpha combination therapy in patients with advanced hepatocellular carcinoma. We tested whether IFNAR2 expression in peripheral blood mononuclear cells could predict the response to 5-FU + IFN.Methods: Predictive factors for survival and response to therapy were determined in 30 patients with advanced hepatocellular carcinoma who underwent treatment with 5-FU + IFN. IFNAR2 expression in peripheral blood mononuclear cells was measured in 11 of the 30 patients.Results: With a mean number of 4.2 courses of combination therapy, one patient (3%) showed a complete response, eight (27%) showed partial responses, 13 (43%) had stable disease, and eight (27%) showed progressive disease. The median survival time of responders (complete response/partial response) was 12.7 months and that of nonresponders (stable disease/progressive disease) was 7.5 months. The one-year and two-year cumulative survival rates of responders and nonresponders were 87/69% and 40/11%, respectively (P = 0.019). Multivariate analysis identified response to therapy (P = 0.037) as the sole independent determinant of survival. The expression level of IFNAR2 in peripheral blood mononuclear cells was significantly (P = 0.012) higher in responders (6.5 ± 2.4) than in nonresponders (2.4 ± 0.6), even though no clinical factors were identified as being associated with the response to the combination therapy.Conclusion: IFNAR2 expression in peripheral blood mononuclear cells may predict the response to 5-FU + IFN therapy in patients with advanced hepatocellular carcinoma, although these data are preliminary.Keywords: interferon, 5-fluorouracil, hepatocellular carcinoma, receptor